2014
DOI: 10.1097/mcg.0000000000000026
|View full text |Cite
|
Sign up to set email alerts
|

Savary Dilation is a Safe and Effective Long-term Means of Treatment of Symptomatic Cricopharyngeal Bar

Abstract: On follow-up from first dilation, 65% patients had statistically significant improvement in FOSS lasting for at least 6 months. Savary dilation seems to be a safe and effective treatment for symptomatic CP bar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Historically, CPB has been treated with dilation, botulinum toxin injection, or open surgery [ 8 ]. A study by Patel BJ et al showed that Savary dilation is both safe and effective, with most patients (81%) free of symptoms at six months [ 4 ]. In another study, Brigand C et al reported similar outcomes for balloon dilation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, CPB has been treated with dilation, botulinum toxin injection, or open surgery [ 8 ]. A study by Patel BJ et al showed that Savary dilation is both safe and effective, with most patients (81%) free of symptoms at six months [ 4 ]. In another study, Brigand C et al reported similar outcomes for balloon dilation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPBs result from the hypertrophy, myositis, and fibrosis of the cricopharyngeal muscle, which reduces the maximal dimension of the upper esophageal sphincter, despite normal relaxation of the sphincter [ 3 ]. First-line therapy for CPB is esophageal dilation with a large bougie or balloon, with surgical myotomy reserved for cases intractable to dilation [ 4 , 5 ]. However, with the success of per-oral endoscopic myotomy (POEM) for Zenker’s diverticulum (z-POEM), per-oral endoscopic cricopharyngotomy (c-POEM) seems like a natural extension of the technique [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limited series reported higher rates of symptomatic improvement in 9 of 10 patients (90%) with similar dilatation techniques (18-20 mm)[9]. Patel et al[13] recently reported a larger experience with 31 patients undergoing Savary dilation with 45 French to 60 French size dilators. In this study, 65% of patients had significant improvement for at least 6 mo using a functional outcome swallow score.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, management has relied upon surgical CP myotomy[5-7]. Endoscopic dilatation poses an attractive option, given the risks associated with myotomy; however, published case series to date have included very small numbers of patients with varying dilatation techniques[8-13]. The aim of our study was to determine the efficacy and safety of through-the-scope (TTS) balloon dilatation of the upper esophageal sphincter (UES) in patients with CPD and to compare the traditional static technique of sequential distention of the balloon with a brusque “pull-back” retrograde approach across the UES.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients with OPD can be managed conservatively with swallowing exercises, rheological modification of the diet, swallowing maneuvers such as a head turn or chin tuck, and possibly neuromuscular stimulation. Certain specific structural conditions can be treated with a targeted surgical procedure such as upper esophageal dilation, cricopharyngeus muscle myotomy (CPM), or botulinum toxin injection, laryngeal framework surgery, or hypopharyngeal diverticulectomy/diverticulotomy . Nonoral enteral nutrition via gastrostomy is frequently necessary in severe cases.…”
Section: Introductionmentioning
confidence: 99%